Analisis Pengaruh Kepemilikan Blockholder, Kepemilikan Manajerial, Kepemilikan Institusional, dan Komite Audit terhadap Nilai Perusahaan - Iwan Wirawardhana; Meco Sitardja (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
The aim of this study is to analyse the effect of Blockholder Ownership, Managerial Ownership, Institutional Ownership, and Audit Committee towards Firm Value. The background of this research is the agency theory and ownership theory. The population in this study are 46 property companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2016. By using purposive sampling technique, 35 companies are qualified as data samples. This research uses the random effect model as the estimation model and multiple regression as the method of analysis. The results of this study shows that Institutional Ownership has a positive effect on Firm Value. Meanwhile, Blockholder Ownership, Managerial Ownership, and Audit Committee have no effect on Firm Value. Moreover, the F-test implies that the variables, blockholder ownership, managerial ownership, institutional ownership, and audit committee, simultaneously influence firm value.